Five-Level Diode-Clamped Inverter With Three-Level Boost Converter - Rosmadi, Abdullah; Nasrudin, Abd Rahim; Siti Rohani, Sheikh Raihan; Abu Zaharin, Ahmad (IEEE USA, 2014)
This paper proposes an active front-end solution to balance the dc-link capacitor voltage of the five-level diode clamped inverter. Capacitor voltage balancing is performed by a three-level boost converter connected to the two inner capacitors of a five-level diode-clamped inverter and additional balancing circuits at the other two outer capacitors. The proposed configuration is tested through simulation and experiment for various load power factor conditions at a high modulation index. The result demonstrates the reliability of the proposed configuration to balance the dc-link capacitor voltage at the desired level.